7. IMPLEMENTASI PROGRAM GERDU KEMPLING DI KOTA SEMARANG - Cahyanto, Herbasuki Nur (Faculty of Social and Political Sciences Diponegoro University, 2014)
Aim of this research is to decribe the implementation process of Gerdu Kempling in Kota Semarang and to identify obstacles during the process. Gerdu Kempling is basically a top down program from Kota Semarang in order to curb poverty. It is a top down program in a sense that initiative to include community participation was coming from the Government. In order to discuss the process, this paper was conducting through implementation theories from Van Meter and Van Horn, Edward III, Mazmanian and Sabatier, and Grindle. Research approach of this paper is qualitative approach with its locus in Kelurahan Tembalang Kota Semarang. The research concludes that supports in the program are varied. For instance, support from BNI is related to economic program such as cows, goats, and money to support micro finance activities; Â whereas support from government institution namely Disnakertrans is in a form of trainings. The main obstacles of the implementation process are community mindset of the program (that it is a grant) and the unclear formation of communication. Therefore, continuos intensive dialogs to program recipients are needed especially to clarify that the supports are not grants and that it has to be shared with other members. In order to develop better communication form, it needs coordination among stakeholders. Coordination can be started from planning process to monitoring and evaluation stage. Evaluation can be done through the help of the program recipients themselves.